A plural indefinite quantifier on the Romance-Slavic border. (July 2021) - Giudici, Alberto; Zanini, Chiara
Abstract : This study investigates the plural form uni/une deriving from the numeral 'one' in the Istriot dialect of Sissano. Sissano is located in the Istrian peninsula, an area characterized by high intensity of linguistic contact. We argue that the rise of such a peculiar form is indeed induced by contact with Croatian and that uni/une is unique in the Italo-Romance domain since, generally, the plural indefinite forms derived from the Latin numeral 'one' are pronouns and never occur in attributive position. The use of uni / une is not attested in the few grammars of Istriot varieties because it is recent and still undergoing a process of grammaticalization. Therefore, we conducted interviews to verify how and to what extent contact with Croatian affects the meaning and the use of uni/une in Sissano. We found that this form is mostly used as a quantifier, bearing mainly the meaning 'a pair of', 'one group of', in the context of pluralia tantum and plural dominant nouns. We further observe that this quantifier has achieved a more advanced stage of grammaticalization in the younger generation of speakers than in the older ones. We discuss the role played by pluralia tantum as well as by the growing prestige of Croatian in triggering this borrowing and in fostering the grammaticalization process of uni/une on its way to become a marker of indefiniteness.